Pile behaviour due to excavation induced lateral soil movement - Yee, See Fong. (2008)
The effect of lateral soil movement on existing piles is known to be a geotechnical problem when engineering any excavation or fill projects on soft soil. When dealing with pile design on soft soil undergoing lateral soil movement, additional considerations must also be given to the pile capacity to withstand the additional soil pressure during the construction period. The factors known to affect the pile integrity are complex and these depend on the pile properties, pile head fixity conditions, soil type, pile group configuration, magnitude of lateral soil movement, soil-movement profile and pile-soil-pile interaction.